TINJAUAN ATAS PROSEDUR PEMBAYARAN GAJI KARYAWAN PADA RUMAH SAKIT PURI CINERE - Idola Natalia (2020)
The purpose of this final project is to review the procedures for paying employee salaries at the Puri Cinere Hospital. The purpose of employee salary payment procedures is to find out the salary payment process for employees. The process of paying employee salaries is done by transfer to the employee's bank account. Puri Cinere Hospital has three elements of salary payment procedure activities. Documents related to the process of payment of employee salaries. The relevant part is the procedure for paying employee salaries at the Puri Cinere Hospital. Accounting records used in employee salary payment procedures. Payroll salaries are paid once every month. With the procedure, a company can carry out its activities by the policies set by the company.